Stage Duration as an Emergent Property: Influence of Mortality and Variation in Environment on Copepod Population Dynamics. - Kitan, S. (M.Sc. Thesis, Dalhousie University, Halifax, Nova Scotia, Canada., 2018)
A key species in the Northwest Atlantic food web is Calanus finmarchicus, which provides an important food source for many marine animals. To better understand its ecosystem roles, obtaining detailed knowledge of its life processes, such as development and mortality, and the factors controlling them is vital. Since pelagic systems are dynamic, variable, and advective, mortality cannot be measured in situ, and development is observed in constant laboratory conditions. Here, a series of modelling studies are conducted to investigate mortality and development separately, by applying and examining common methodologies and providing new approaches and recommendations, and explore the interaction of processes, by building an individual-based model to simulate the life history of C. finmarchicus. This model is presented with enhanced capabilities for coupling physical ocean data and tested with a case study that investigates the influence of environmental variability and mortality on simulated population dynamics in space and time.